Analisis Bibliometrik Penelitian Tugas Akhir Mahasiswa di Fakultas Ekonomika dan Bisnis Universitas Gadjah Mada - Maryatun Maryatun; Wuri Handayani (Perpustakaan Nasional, 2022)
The results of research in universities are expected to contribute to the development of science and technology and can provide benefits for the welfare of society. This study aims to map out topics from the 2020 student final project research to evaluate the achievement of the vision and mission of the Faculty of Economics and Business, Universitas Gadjah Mada. The research method used is a quantitative method with bibliometric analysis, namely mapping research topics based on co-word analysis. Data processing using VOSviewer. The results showed that the research theme for the final project of students from each department was in accordance with the flagship research theme of FEB UGM. The research theme for the final project of the Accounting Department students has conformity to clean organizational governance to create people with integrity, 71%, with dominant topics, Corporate Social Responsibility, internal control, performance, and Unified Theory of Acceptance and Use of Technology. The research theme for the final project of the students of the Department of Economics is that it is compatible with sustainable economic growth based on local wisdom, amounting to 63.9% with dominant topics, economic growth, unemployment, fixed effects, Autoregressive Distributed Lags, and the cost approach. Furthermore, the research theme for the final project of the Management Department students has conformity to the development of science-based innovation and information technology to improve quality education and research, by 61%, with dominant topics, abnormal returns, analysis of five forces porter, bank, business model canvas, leadership, and purchase intention.